PENGARUH MODEL PEMBELAJARAN DECISION MAKING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA-BIOLOGI MATERI POKOK SISTEM GERAK PADA TUMBUHAN - Seli Fitri (TUNAS : Jurnal Pendidikan Biologi, 2023)
The aim of the research is to determine the effect of the Decision Making learning model on students’ cognitive learning outcomes. One solution to influence student learning outcomes, especially in the material on movement systems in plants, is through a Decision Making model that involves students directly, both individually and in groups, in learning activities. This research method is a quasi-experimental method which is quantitative, namely in the experimental class the Decision Making model is used, while in the control class the conventional method is used. The research results stated that in the control class the average learning outcomes on the pretest were sufficient and the average learning outcomes were good on the posttest. Meanwhile, in the experimental class by carrying out the pretest the average learning outcomes were sufficient and in the posttest the average learning outcomes were very good. The research conclusion based on hypothesis test calculations is that tcount is significantly greater than ttable. Because tcounts ttable, Ha is accepted and Ho is rejected, which means "there is an influence of the Decision Making learning model on student learning outcomes". The researcher’s advice is for every Biology subject teacher to apply the Decision Making learning model in order to improve students’ abilities, as well as improve teaching and learning methods and become reference material for future researchers who are relevant to this research.